K metaforám v Babičce po pitvě z hlediska kognitivní lingvistiky - Zábranský, Lukáš (Slavia Occidentalis, 2013)
The author examined metaphorical concepts in this Czech parody of the famous work by Božena Němcová (The Grandmother). Based on excerpts, an analysis of metaphorical concepts was conducted. Whenever possible, the author took etymology into account during the research. „Babička po pitvě” (BPP) is a parody, as indicated already by its very title. Assurance comes with the finding of a mirrored condensed morphology of BPP with respect to the original. Both BPP and The Grandmother contain 18 chapters and four identical plot lines. To parody the original, Hynek uses formal sentence structures, simple syntax prevails, often exacerbated to the extreme, thus giving a simplified and scholarly limited impression. The characters in BPP are exposed as: ethnocentric, naive, limited, religious, belonging to a foreign language affiliation, vulgar, capricious, altruistic, sexually unsatisfied or only temporarily satisfied. The image of the world in Staré bělidlo (Old Bleaching Ground) is: prejudiced, superstitious, anthropocentric, subjective, superficial, limited, firmly grounded in the natural cycle and traditions associated with it. Procedures and traditional findings of cognitive linguistics/ language picture of the world have been positively verified. The morbid, Erotic, socially incorrect, cynical, dissonant as well as poetic and gentle satire of BPP thus represents an eccentric and rich foam of comedy, however, under its thick surface we find more serious content, raising social, moral and value issues; using parody, BPP thus fundamentally challenges the traditional values demonstrated in The Grandmother.